After Derrida : literature, theory and criticism in the 21st century - Rabaé, Jean-Michel (After series, 2018)
'It is important for the materialist historian, in the most rigorous way possible, to differentiate the construction of a historical state of affairs from what one customarily calls its 'reconstruction.' The 'reconstruction' in empathy is one- dimensional. 'Construction' presupposes 'destruction.' Almost fourteen years after the death of Jacques Derrida, the least one can say is that his inheritance is as contested and fraught with rivalries, rejections, and appropriations as at the time of the flowering of Deconstruction in American universities in the seventies and eighties. A halt was observed in 1988-89 after the posthumous revelations about Paul de Man's past in Belgium and Derrida's embattled defense of his friend. Today, in France, one often hears that 'Derrida a fait l'Ecole mais n'a pas fait ecole,' meaning that Derrida passed the entrance examination of the prestigious Ecole Normale Superieure where he taught for a long time, where he met Paul Celan, Louis Althusser, Michel Foucault and many other luminaries, whereas he never had a real 'school' in France-no real institutional backing beyond the various Parisian places at which he taught later, or those that he founded like the College de Philosophie; his following constituted of young philosophers, only a few of whom became university professors in their turn and disseminated his teachings. However, the mechanisms of power within the French university remained closed to Derrida until the end; besides, he wanted to prevent the stereotyped reproduction currently observed from master to disciple'--
Keywords: Derrida, Jacques; Derrida, Jacques : Influence; kirjallisuus; kritiikki; kirjallisuuskritiikki; historia; litteratur; kritik; litteraturkritik; Critical theory; Literature : History and criticism; Critical theory